2019
DOI: 10.1590/fst.24418
|View full text |Cite
|
Sign up to set email alerts
|

A fast drying method for the production of salted-and-dried meat

Abstract: The objective of this work was to investigate the application of microwave vacuum drying (MWVD) as a fast drying method to produce salted-and-dried beef cuts. Moreover, aiming to reduce the sodium content in the meat product, the partial replacement of NaCl by KCl during the salting stage was also investigated. To this end, beef cuts were salted by immersion in one of three saline solutions before drying: Solution A-100% NaCl; Solution B-75% NaCl and 25% KCl; and (iii) Solution C-50% NaCl and 50% KCl. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Several authors have reported the effects of incorporating vacuum treatments in the salting and marinating processes of different kinds of foods, obtaining favorable yields. Nevertheless, they use higher temperatures, salt solution concentrations, and contact areas than those used in this study, among other variables, corroborating the marked influence of the process conditions on the effect of the applying vacuum treatment (Bampi, Schmidt, & Laurindo, 2019; Chiralt et al, 2001; Corzo & Bracho, 2007; Jin et al, 2014; Mújica‐Paz, Argüelles‐Piña, Pérez‐Velázquez, Valdez‐Fragoso, & Welti‐Chanes, 2006; Serio et al, 2017; Tomac, Rodríguez, Perez, Garcia, & Yeannes, 2020; Wang, Xu, Kanga, Shen, & Zhanga, 2016). Deumier, Bohuon, et al (2003) reported that the number of pulses affected the water and salt mass gain differently.…”
Section: Resultssupporting
confidence: 82%
“…Several authors have reported the effects of incorporating vacuum treatments in the salting and marinating processes of different kinds of foods, obtaining favorable yields. Nevertheless, they use higher temperatures, salt solution concentrations, and contact areas than those used in this study, among other variables, corroborating the marked influence of the process conditions on the effect of the applying vacuum treatment (Bampi, Schmidt, & Laurindo, 2019; Chiralt et al, 2001; Corzo & Bracho, 2007; Jin et al, 2014; Mújica‐Paz, Argüelles‐Piña, Pérez‐Velázquez, Valdez‐Fragoso, & Welti‐Chanes, 2006; Serio et al, 2017; Tomac, Rodríguez, Perez, Garcia, & Yeannes, 2020; Wang, Xu, Kanga, Shen, & Zhanga, 2016). Deumier, Bohuon, et al (2003) reported that the number of pulses affected the water and salt mass gain differently.…”
Section: Resultssupporting
confidence: 82%
“…For all temperatures it was noted that in the last hours of salting there was a not significant slight variation in the values of ∆E (between 0.14 to 1.29 units). Bampi, Schimidt and Laurindo (2019) [50] salted beef with reduced sodium content and found values of global color difference between 7.79 to 14.15, in which the increase in the salt content used during the process promoted more considerable color change. Still in the study by Bampi, Schimidt and Laurindo (2019) [50], ∆E values between 6.0 and 12.0 show a massive color difference, and above 12.0 units, the difference is classified as very large.…”
Section: Physicochemical Changes During the Dry Salting Kineticsmentioning
confidence: 99%
“…Bampi, Schimidt and Laurindo (2019) [50] salted beef with reduced sodium content and found values of global color difference between 7.79 to 14.15, in which the increase in the salt content used during the process promoted more considerable color change. Still in the study by Bampi, Schimidt and Laurindo (2019) [50], ∆E values between 6.0 and 12.0 show a massive color difference, and above 12.0 units, the difference is classified as very large. This global variation is a result of the variations observed in the parameters L*, a*, and b* (data not shown, used by Equation 5 to calculate ∆E).…”
Section: Physicochemical Changes During the Dry Salting Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydration number is also a factor affecting the diffusion rate of the molecule. The ions possessing higher hydration numbers bind more water; thus, solvent molecules readily hinder the hydrated ions, resulting in a lower diffusion rate of the molecule which prevents it from diffusing to an environment with low ionic power (Bampi et al, 2019). Na + ions possess higher hydration number than K + ions, and therefore, cause a lower diffusion rate (Bampi et al, 2019;Zhang et al, 2020).…”
Section: Effective Diffusion Coefficientmentioning
confidence: 99%